The influence of tail chain length on oil film detachment: C2nTAB series (n = 4 − 9). (2nd November 2022) - Zhou, Lixia; Yan, Youguo; Song, Wenhao
Abstract: Employing molecular dynamic simulations, the detachment process of oil film from silica surface in six cationic surfactants with same head group and different alkyl tail length was investigated. In this work, the surfactant C2n TAB series ( n  = 4 − 9) were selected to investigate the effect of tail chain length on oil detachment capability. In all surfactants systems, the oil film detachment processes undergone three stages: at initial stage, the surfactants adsorb on the oil-water interface. And then water molecules penetrate the oil film and form a water channel. At last stage, the water molecules spread on the silica surface and the oil film are detached gradually. Quantitative evaluation indicates that the detachment capability of these three surfactants follows C12TAB > C14TAB ≈ C16TAB≈C8TAB > C10TAB > C18TAB. Our results indicated that the chain length of surfactant play important role in tertiary oil recovery, and a compatibility should be considered.